New Frontiers in Anaerobic Digestion (AD) Processes - Heaven, Sonia; Kusch-Brandt, Sigrid; Banks, Charles (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue explores recent developments and advanced concepts related to the valorisation of organic wastes and other biomass through the application of anaerobic digestion (AD). Biological phenomena, the efficiency of the AD process, the viability of full-scale AD installations, the integration of hydrogen and biomethane concepts, and biorefineries are some of the themes covered. While AD is addressed under different perspectives, the results all strengthen AD to fulfil its important role as a sustainable and highly versatile technology. Further research and development needs are also presented.